Disasters While Digging: Rates of Violence Against Mine Workers in Democratic Republic of Congo, South Africa, and Zambia - Christian Freymeyer (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
In 2010, violence broke out at a mine in Zambia and many local workers were injured. This incident served as a jump-off point for criticism of Chinese mines in Africa and a broader discussion of the treatment of workers by Chinese managers and companies. But is there actually a higher rate of violence against workers in Chinese-owned mines? In this brief, Christian Freymeyer explores rates of violence against workers in mines in Democratic Republic of Congo, South Africa, and Zambia, and further dissects the idea of mine ownership to help answer this question.
Keywords: 330